Differentiating indexation in Dutch pension funds - Roel M. W. J. Beetsma; Alessandro Bucciol (Center for Economic Studies and ifo Institute (CESifo), 2010)
We investigate numerically how indexation of funded pensions for inflation can be differentiated across the various groups of fund participants. The pension arrangement is modelled after the Dutch situation. While the aggregate welfare consequences are small, group-specific consequences are more substantial with the workers and future born losing and retirees benefitting from a shift away from uniform indexation. Those welfare shifts result from systematic redistribution of welfare rather than shifts in the benefit of risk sharing provided by the system.
Keywords: H55; I38; C61; 330; indexation; funded pensions; welfare effects; pension buffers; stochastic simulations; Pensionsfonds; Inflation; Umlageverfahren; Rentenreform; Gesetzliche Rentenversicherung; Wohlfahrtseffekt; Niederlande